2009
DOI: 10.1111/j.1365-3024.2009.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of CD8+ T cells expressing granzyme A is associated with lesion progression in human cutaneous leishmaniasis

Abstract: Human infection with Leishmania braziliensis leads to the establishment of cutaneous leishmaniasis (CL), characterized by the appearance of skin lesions that progress from nonulcerated to ulcerated forms. Our goal was to characterize the immunological kinetics associated with this progression, comparing the cellular composition, cytokines and granzyme expression between lesions of patients with early (E-CL) and late stages (L-CL) of CL. Histopathological analysis showed that lesions from L-CL had more exuberan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(156 citation statements)
references
References 27 publications
9
143
2
2
Order By: Relevance
“…This is in line with the association of IFN-cproducing CD4 + T cells and the healing of lesions observed in murine experimental CL (4). In contrast, the role of CD8 + cells for healing in human CL is controversially discussed ranging from beneficial to no effect (7), or even enhancement of lesion ulceration (8). Our present study corroborates earlier reports that suggest that antigen-specific CD8 + T cells alone are not sufficient for the clearance of CL.…”
Section: Results and Conclusionsupporting
confidence: 82%
“…This is in line with the association of IFN-cproducing CD4 + T cells and the healing of lesions observed in murine experimental CL (4). In contrast, the role of CD8 + cells for healing in human CL is controversially discussed ranging from beneficial to no effect (7), or even enhancement of lesion ulceration (8). Our present study corroborates earlier reports that suggest that antigen-specific CD8 + T cells alone are not sufficient for the clearance of CL.…”
Section: Results and Conclusionsupporting
confidence: 82%
“…Chronic dermal leishmaniasis has been associated with immunological hyperreactivity (5,6), overproduction of pro-and anti-inflammatory cytokines (21), and scarce but persistent parasites at the lesion site (4). Upregulation of inflammatory functions is accompanied by increased cellular infiltration of lesions, perpetuating the immunopathology (23,24). We have previously shown that macrophage permissiveness for survival and replication of intracellular Leishmania correlates with the clinical outcome of infection; macrophages from patients with chronic CL were more permissive to infection than were cells from individuals with asymptomatic disease (25).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, cytotoxic activity was higher in CD8 + T cells at the late stage of differentiation in patients with more severe forms of cardiac disease, whereas the production of IL-2 in CD8 + T cells was lower. Studies have shown that the severity of the disease, that is, tissue damage, resulting from Leishmania braziliensis infection is directly correlated with more granzymeproducing CD8 + T cells (76) and that CD8 + T cell-mediated cytotoxicity promotes lesions in cutaneous leishmaniasis (77). In addition, CD8 + T cells producing perforin might play a detrimental role in experimental T. cruzi infection in mice, leading to heart injury (78).…”
Section: Cd8mentioning
confidence: 99%